Causes of admission, length of stay and outcomes for common kestrels in rehabilitation centres in the Czech Republic - Lukesova, Gabriela; Voslarova, Eva; Vecerek, Vladimir; Vucinic, Marijana (Scientific reports, 2021)
Rehabilitation centres help injured animals to recover and return back to the wild. This study aimed to analyse trends in intake and outcomes for the common kestrels (Falco tinnunculus) admitted into rehabilitation centres in the Czech Republic. From 2010 to 2019, a total of 12,923 kestrels were admitted to 34 rehabilitation centres with an increasing trend (rSp = 0.7697, P < 0.01) being found during the monitored period. Subadult kestrels (34.70%) and kestrels injured by power lines (26.57%) were most often admitted. Most kestrels in the rehabilitation centres died or had to be euthanized (81.66%), only 15.90% of the birds could be released back into the wild. The median length of stay in rehabilitation centres for kestrels that were subsequently released was 35 days. Considering survival rates, the most critical threat to kestrels was poisoning (100% of the cases resulted in death) but mortality of the kestrels admitted for most other reasons also exceeded 80%. Given the low success rate of the care of kestrels in rehabilitation centres and the relatively small proportion returned to the wild, it is essential to eliminate the causes leading to their admission, that is, to protect their natural habitats and to prevent unnecessary capture.
Keywords: zachování přírodních zdrojů; Animals; řízení veterinární praxe; Conservation of Natural Resources; výsledek terapie; Hospitals, Animal; Time Factors; časové faktory; Animal Husbandry; divoká zvířata; nemocnice veterinární; Practice Management, Veterinary; nemoci ptáků; Treatment Outcome; Bird Diseases; Falconiformes; Animals, Wild; Czech Republic; Česká republika; zvířata; chov zvířat